2017
DOI: 10.13057/biodiv/d180225
|View full text |Cite
|
Sign up to set email alerts
|

A biophysical observation of Mahakam River around Tanjung Una of Kutai Kartanegara, Indonesia

Abstract: Abstract. Suyatna, I, Mislan. A. Rahman A. Winta Wijaya YI. 2017 Kartanegara,. The aim of this study is to dig up more information about the biophysical conditions of Mahakam River around Tanjung Una of Kutai Kartanegara, Indonesia including the fishery potential in these locations. The observations were conducted in two periods. Through field surveys, the sample of fish and shrimp were caught with pulled nets from many stations, while to know the water quality around the location of the observation, water sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…All marine fish species found both in the lower and middle part of Mahakam was known to distribute along coastal and sea waters of Makassar strait from southern to northern of Panajam Paser Utara district (Bappeda and Fpik Unmul, 2017), Kutai Kartanegara district (Suyatna et al, 2010), Bontang city (Suyatna et al, 2016) and Sangatta Utara district (Juliani and Suyatna, 2014). Both marine and freshwater fish species in the lower part of Mahakam was also reported in the result of a biophysical observation of Mahakam river (Suyatna et al, 2017).…”
Section: Fish Structure Communitymentioning
confidence: 88%
“…All marine fish species found both in the lower and middle part of Mahakam was known to distribute along coastal and sea waters of Makassar strait from southern to northern of Panajam Paser Utara district (Bappeda and Fpik Unmul, 2017), Kutai Kartanegara district (Suyatna et al, 2010), Bontang city (Suyatna et al, 2016) and Sangatta Utara district (Juliani and Suyatna, 2014). Both marine and freshwater fish species in the lower part of Mahakam was also reported in the result of a biophysical observation of Mahakam river (Suyatna et al, 2017).…”
Section: Fish Structure Communitymentioning
confidence: 88%
“…Suyatna et al (2010) identified 43,340 fish caught by minitrawl and noticed 131 species from 87 genera, 61 families and 10 orders. A total of 13 species were observed in Mahakam river 40 km behind the river mouth (Suyatna et al, 2017b), and among of them, the longfin anchovy Setipinna sp., was found 230 km from the coastline (Suyatna et al, 2017c). Fish found in the Mahakam delta were also recognized along the coastal waters of East Kalimantan.…”
Section: Introductionmentioning
confidence: 99%